EXTENT:a portable programming environment for designing and implementing high-performance block recursive algorithms - Dai, D L; Gupta, S K S; Kaushik, S D; Lu, J H; Singh, R V; Huang, C H; Sadayappan, P; Johnson, R W (Conference on High Performance Networking and Computing: Proceedings of the 1994 ACM/IEEE conference on Supercomputing : Washington, D.C.; 14-18 Nov. 1994, 1994)
EXTENT is an EXpert system for TENsor product formula Translation. In this paper we present a programming environment for automatic generation of parallel/vector programs from tensor product formulas. A tensor (Kronecker) product based programming methodology is used for designing high performance programs on various architectures. In this programming methodology, block recursive algorithms such as the fast Fourier transform and Strassen's matrix multiplication algorithm are expressed as tensor product formulas involving tensor product and other matrix operations. A tensor product formula can be systematically translated to parallel and/or vector code for various parallel architectures. A prototype system which generates programs for the Cray Y-MP, Cray TSD, and Intel Paragon has been developed. Performance results for some generated programs are presented.